Família, escola e intervenção fonoaudiológica: suas mediações com o surdo - Machado, Aline Dubal (2005)
This work had for intention to analyze the established mediations for the teacher s listeners, for the phonoaudiology trainees and for relatives of deaf that frequent the school in a concomitant way to the phonoaudiology attendance. The development of that research felt in Serviço de Atendimento Fonoaudiológico (SAF) of the Phonoaudiology course of Universidade Federal de Santa Maria (UFSM) and in two schools of that municipal district. That study treats of a research of the type etnográfica, descriptive and quantitative. To begin her, they were selected subject of three different segments: teachers, phonoaudiology trainees and family of deaf. The same ones were identified starting from a previous selection among the deaf ones that frequented phonoaudiological therapy while attending school. The data were obtained starting from an interview structured with the purpose of investigating the mediations of the subjects in function of three categories: deafness, interaction and communication. That research had your approval for the Committee of Ethics in Research of UFSM. It was considered pertinent to end that teachers listeners, phonoaudiology trainees and family: in your mediations, in the context of the deafness, they are evidencing the influence of the auditory loss in the pedagogic use of the deaf, your interaction with the other subjects and your communication; in your mediations, they are understanding in a different way deaf subject's image, to which the teachers listeners denote larger emphasis than the other segments; however, different and normal subject's images are just internalized for the family segment; they choose to Libras as the middle of ideal communication for the deaf subject and, however, they make use of the speech close to Libras as tool of your mediations on behalf of a contact more cash of the deaf with the other communities; they detach the importance of the deaf subject's interaction with the other subject of the social context, to which they are inserted through to Libras used of concomitant form to the speech; they don't believe in the deaf subject's insert in the society.